Acceso a la prestación humanitaria periódica para las víctimas del conflicto armado en Colombia (2018)
The present study has the purpose of examining the conditions of access to the periodic humanitarian benefit for the victims of the armed conflict, which has the purpose of repairing the impairment that a disabled person has, as a result of the armed conflict, the Colombian state is socially based and democratic law, which is necessary to guarantee the fundamental rights of social interest, that is, through affirmative actions seeks to restore the right of passive subjects of the social phenomenon of armed conflict, because of such social problem, has been It is necessary to identify the conditions of access to the periodic humanitarian provision for the victims of the armed conflict, this to provide information that helps to minimize the negligence with respect to the provision of services for the procedure, which today is present in the Colombian legislation in seeking to provide equality guarantees, dign Humanity, the vital minimum to the vulnerable population today victims of the internal conflict.